Sala Weinlös and Irena Krampner, students of Hugo Steinhaus and Kazimierz Twardowski - Banakh, I. (Matematychni Studii, 2025)
The motivation for writing this article was the discovery of photographs of Sala Weinlös and Irena Krampner. For mathematicians, the first one is especially valuable, as it is the only known photograph of the only woman who earned a doctorate in mathematics in Lviv before World War II. The archival findings presented here complement the few existing publications about Sala Weinlös and introduce another female student of the University of Lviv also highly successful in mathematics, Irena Krampner, who completed a doctoral dissertation in philosophy. In the 1920s--1930s, professors Hugo Steinhaus and Kazimierz Twardowski played a~significant role in their education and shaping their subsequent careers.